2023
DOI: 10.3390/ijerph20065126
|View full text |Cite
|
Sign up to set email alerts
|

Local Fiscal Pressure and Public Health: Evidence from China

Abstract: Under the dual challenges of global downward economic pressure and the COVID-19 pandemic, studying the impact of local government fiscal pressure on public health is a meaningful endeavor. First, this paper analyzes the impact of local government fiscal pressure on public health and clarifies its impact mechanisms. Second, by utilizing panel data of 31 Chinese provinces from 2000 to 2020, two-way fixed-effects and mediating-effects models are developed to identify the effects and impact mechanisms of local gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…When local governments have insufficient financial resources of their own and must rely on financial assistance from the central government to fulfill their responsibilities for authority expenditure, the effectiveness of local public goods provision is impaired (46,47). Some studies have found that fiscal decentralization can empower local governments to meet the public preferences of residents in their jurisdictions in a timely manner (48), and that expanding the taxation power of local governments can improve local healthcare services by optimizing the structure of fiscal expenditure (49,50). An appropriate degree of fiscal autonomy can also help promote HED.…”
Section: Analysis Of the Driving Factors Of The Coupling Coordination...mentioning
confidence: 99%
“…When local governments have insufficient financial resources of their own and must rely on financial assistance from the central government to fulfill their responsibilities for authority expenditure, the effectiveness of local public goods provision is impaired (46,47). Some studies have found that fiscal decentralization can empower local governments to meet the public preferences of residents in their jurisdictions in a timely manner (48), and that expanding the taxation power of local governments can improve local healthcare services by optimizing the structure of fiscal expenditure (49,50). An appropriate degree of fiscal autonomy can also help promote HED.…”
Section: Analysis Of the Driving Factors Of The Coupling Coordination...mentioning
confidence: 99%